Transient thermal model of nanosecond pulsed laser ablation: Effect of heat accumulation during processing of semi-transparent ceramics. (July 2021) - Cha, D.; Axinte, D.
Highlights: A difference between single and multi pulse ablation threshold has been observed. A thermal model for multi pulse ablation has been developed. The model accounts for temperature dependent properties and absorption coefficient The model highlights the importance of heat accumulation during multi-pulse ablation. Abstract: Nanosecond ablation of semi-transparent ceramics represents a particularly interesting scenario where non-linear absorption mechanism allows absorption of laser energy for photon energy below the band gap of the material. Yttria Stabilized Zirconia (YSZ) ablated by infrared radiation represents as an example of such scenario. Ablation threshold experiments reveal a stark difference between the behaviour observed during ablation of single pulses compared to multiple pulses. During single pulses, a statistical occurrence of ablation is observed. For laser intensity below the dielectric breakdown threshold, this phenomenon has been explained on the basis of a defect-mediated thermal runaway which causes an exponential increase of the bulk material absorption coefficient as function of temperature. To investigate this phenomenon, and its effect during multi-pulse ablation, a 1D modelling framework has been developed and validated. The framework focuses on simulation of ablation of trenches (i.e. partially overlapped pulses) considered as convolution of single pulses, and account for the governing equation of heat diffusion, vaporization, plasma shielding, volumetric absorption and temperature-dependent absorption coefficient by use of a simplified defect mediated absorption model which represents the main novelty of the paper. The application of the model for various laser processing parameters reveals the importance of heat accumulation on the process. A positive feedback mechanism is established over successive pulses which leads to the material becoming progressively more absorbing, and eventually results in material removal through ablation. This phenomenon explains the sharp ablation threshold observed experimentally during ablation of trenches. The modelling framework also reveals interesting dynamics caused by the temperature dependence of the material absorption behaviour, such as a delay in the starting time for material removal, and drastic changes in the energy distribution within the sample throughout the duration of a laser pulse. Ultimately, the effect of heat conservation, which is often neglected, has been shown to represent a key dynamic during multi-pulse ablation, and should be accounted for during simulations of real-world laser processes, in particular for low diffusivity semi-transparent materials.